2013
DOI: 10.1097/sap.0b013e31824c9073
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Negative-Pressure Wound Therapy Versus Conventional Dressings Following Abdominal Wall Reconstruction

Abstract: This study suggests that incisional NPWT following abdominal wall reconstruction significantly improves rates of wound complication and skin dehiscence when compared with conventional dressings. Prospective, randomized, controlled studies are needed to further characterize the potential benefits of this therapy on wound healing after abdominal wall reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 17 publications
4
121
2
1
Order By: Relevance
“…39%) when compared with conventional dressings. Regardless of the surgical technique employed, in order to prevail over the specifi c obstacles that the repair of complex abdominal wall defects can present, the prophylactic use of NPWT in a continuous suction mode of 125 mmHg for 7 days duration over a closed incision has been shown to improve outcomes [ 29 ] ( Fig. 32.3 ).…”
Section: Negative Pressure Wound Therapy and Special Circumstances CLmentioning
confidence: 98%
“…39%) when compared with conventional dressings. Regardless of the surgical technique employed, in order to prevail over the specifi c obstacles that the repair of complex abdominal wall defects can present, the prophylactic use of NPWT in a continuous suction mode of 125 mmHg for 7 days duration over a closed incision has been shown to improve outcomes [ 29 ] ( Fig. 32.3 ).…”
Section: Negative Pressure Wound Therapy and Special Circumstances CLmentioning
confidence: 98%
“…50,51 Investigators have reported significantly lower rates of wound complications and skin dehiscence with negative pressure wound therapy compared to conventional dressings following abdominal wall reconstruction. 52 Finally, there is some experimental evidence that negative pressure on closed incisions may promote angiogenesis. 49 Other practices we have adopted to reduce SSO are routine placement of drains above and below the repair material and strict avoidance of the use of abdominal binders in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Negative pressure therapy has proven benefits in the management of open wounds, and more recently a negative pressure system has been developed for use on closed wounds at high risk of breakdown [9]. The latter system has proven beneficial in the management of difficult wounds, for instance after abdominoplasty.…”
Section: Introductionmentioning
confidence: 99%